Letter as Subject for Anthropological Research - Jonutytė, Jurga (Tautosakos darbai, 2024)
The article discusses the value and possible results of the anthropological research focusing on ordinary letters. An ordinary letter is considered in the article to be written primarily for maintaining a relationship with the addressee, rather than for solving specific problems in a certain field (even if that includes research, culture, art, business, or legal issues). The anthropological research of ordinary letters is valuable in that it reveals the less visible patterns of communication and cooperation. This analysis primarily displays the temporality of communication and togetherness, showing correspondence as a rhythmic bidirectional continuous process of different intensity; secondly, it highlights the composition of the momentary “I”, which depends on the relationship with the addressee and draws together episodes from different spaces and times; and finally, it discloses the constant negotiations with the proposed or imposed roles – these negotiations are most clearly visible in the ordinary letters and, at the same time, they clearly vary depending on the relationship maintained by the particular thread of correspondence. The article also uses theoretical insights by scholars researching the epistolary materials (Liz Stanley, Helen Dampier, Aistė Kučinskienė) and those by anthropologists and philosophers (William James, Maurice Blanchot, Judith Butler, Jens Brockmeier, Harold Garfinkel, Hanna Meretoja), including the classical theories of time, yet again reminding us of the heterogeneity of the time experience and human actions. The correspondence of the Lithuanian poet Janina Degutytė was chosen as a suitable example, since it most clearly reveals various aspects of the ordinary letters discussed in the article.